Food Experience Design to Prevent Unintended Consequences and Improve Well-being. (February 2022) - Addis, Michela; Batat, Wided; Atakan, S. Sinem; Austin, Caroline G.; Manika, Danae; Peter, Paula C.; Peterson, Lane
This article introduces a novel and comprehensive conceptual framework for designing innovative food experiences that enhance food well-being. We call this framework the novel food experience design. It supports managers in cocreating customer-centric food experiences to limit unintended detrimental consequences and enhance individual and societal food well-being. The novel food experience design (1) employs a systemic (vs. endemic) approach to the innovation process and (2) promotes prioritizing ethical decision-making alongside economic decision-making. Building on insights derived from ecosystem theory and the ethical principles literature, we develop four fundamental propositions to innovate food experiences: do no harm, do good, ensure autonomy, and ensure fairness. Our framework promotes higher levels of individual and societal food well-being than restricted food design innovations, preventing unintended consequences. Finally, we illuminate the implications for service research and practice.